Peran Kompetensi Kewirausahaan Kepala Madrasah dalam Meningkatkan Kesejahteraan Guru di MAN 2 Kudus Tahun Pelajaran 2024/2025 - Uswatun Hasanah; Subaidi, Subaidi; Sukarman, Sukarman (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing demands for teacher professionalism are not always accompanied by adequate welfare, especially in Islamic educational institutions. This study aims to describe the role of the madrasah principal’s entrepreneurial competence in improving teacher welfare at MAN 2 Kudus in the 2024/2025 academic year. Using a qualitative descriptive method, data were gathered through observations, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The study focuses on three aspects: the implementation of entrepreneurial competence, supporting and inhibiting factors, and the outcomes achieved. The findings show that the principal has demonstrated strong entrepreneurial competence, such as innovation, motivation, persistence, and the ability to manage school-based business units. Supporting factors include multiple income sources, high commitment from leadership and the school committee, and the professional status of most teachers. Inhibiting factors involve teacher workload, limitations on government education funds (BOS), and the underperformance of school businesses. Despite challenges, the entrepreneurial competence of the principal has positively impacted teacher welfare in economic, professional, and psychological aspects.